Association of Salt-Reduction Knowledge and Behaviors and Salt Intake in Chinese Population - Han, Bing; Li, Chuancang; Zhou, Yabing; Zhang, Mengge; Zhao, Yang; Zhao, Ting; Hu, Dongsheng; Sun, Liang (Frontiers in Public Health, 2022)
Objective: Excessive salt intake is causally associated with increasing risk of cardiovascular disease. Salt-reduction actions have been rapidly carried out across China since 2017. This study aimed to investigate the association of salt-reduction knowledge and behaviors and salt intake in a Chinese population. Study design: This study was a national cross-sectional study,in China. Methods: This cross-sectional study was based on data collected from Chinese adult chronic disease and nutrition surveillance in 2018, with 7665 study participants included. Salt intake was assessed by calculating 24h urine sodium from morning urine samples. Logistic regression, and mean impact value (MIV) based on the back propagation (BP) artificial neural network were used to screen the potential influencing factors. Results: A total of 7665 people were included in the analysis, of which the average age was 54.64±13.26 years old, and men accounted for 42.6%. Only 19.3% people had known the Chinese Dietary Guidelines, and only 7.3% people accurately stated the salt intake recommended by the Chinese Dietary Guidelines. Approximately 41% of the respondents adopted salt reduction behaviors, among which the number of people who used less salt when cooking was the largest, and the number of people who used low sodium salt was the least. In the logistic regression, only No extra salt was added on the table showed the effect of salt-reduction, the odds ratio (OR) was 0.78 (95%CI: 0.64-0.95). In the result of MIV based on the BP neural network, the most important was less salt when cooking, while Reduce eating out and using salt-limiting tools was the last. Conclusion: The research shows that the popularization of salt-reduction knowledge and behaviors reduced the population's salt intake. However, there was still much room to promote salt-reduction knowledge and behaviors, and the promotion of salt-reduction tools and low-sodium salt still needs to be strengthened.